2003
DOI: 10.1159/000070253
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ATP on Intracellular pH in Pancreatic Ducts Involves P2X<sub>7</sub> Receptors

Abstract: Pancreatic acini release ATP, which can stimulate HCO3--secreting ducts that express purinergic receptors from both P2X and P2Y families. The aim of this study was to investigate whether extracellular ATP affects HCO3- or H+ transport across the plasma membrane of intralobular ducts, and determine which P2 receptors might be involved. Ducts were obtained from rat pancreas, and the pH sensitive fluorophore BCECF was used to measure pHi and recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 31 publications
(40 reference statements)
2
17
0
Order By: Relevance
“…1, right side) [11,20]. As for the ATP/P2X7R pathway, it has also been reported that ATP induced a reduction in intracellular pH in rat pancreatic ducts via P2X7R activation [22]. We further observed that the activation of the P2X7R by ATP induced an increase in lysosomal pH in microglial cells [23], which might have caused a reduction in cytosolic pH by impairing the intracellular proton balance.…”
Section: Acidic Extracellular Ph Acts As a Danger Signal Via Inflammasupporting
confidence: 65%
“…1, right side) [11,20]. As for the ATP/P2X7R pathway, it has also been reported that ATP induced a reduction in intracellular pH in rat pancreatic ducts via P2X7R activation [22]. We further observed that the activation of the P2X7R by ATP induced an increase in lysosomal pH in microglial cells [23], which might have caused a reduction in cytosolic pH by impairing the intracellular proton balance.…”
Section: Acidic Extracellular Ph Acts As a Danger Signal Via Inflammasupporting
confidence: 65%
“…The P2X 7 receptor is a membrane-bound, ligand-operated channel whose main function in epithelial cells is mediation of apoptosis [8][9][10]. The natural ligand of the P2X 7 receptor is adenosine triphosphate (ATP) [8,9], which is present in the extracellular fluid of epithelial cells at high nanomolar and low micromolar levels [11][12][13][14][15]. While ATP requirements of the P2X 7 receptor are higher than those of other purinergic receptors [8,9], the ATP levels in extracellular fluids suffice to activate the receptor [15].…”
Section: Introductionmentioning
confidence: 99%
“…The natural ligand of the receptor is ATP [15,16] which is present in the extracellular fluid of epithelial cells at concentrations that can activate the receptor [4,8,[18][19][20][21]. Binding of ATP to the P2X 7 receptor can activate various cell-specific signaling cascades, including the IL-1β [22], TNFα-TRAIL [23], and the p38, JNK / SAPK [24], and NF-κB cascades [25].…”
Section: Introductionmentioning
confidence: 99%